The Ability of Seventh-Grade Students in Mathematical Problem-Solving on Set Theory Using Animation Media - Faturrohman, Muhammad Habib; Nuraeni, Zuli; Yukans, Septy Sari; Mansur, Nabilah (Edupedia Publisher, 2024)
The importance of mathematical problem-solving skills is so that students can understand mathematical concepts deeply and flexibly, allowing them to apply their knowledge in various problem-solving situations. One of the learning media that can be applied to train students in solving mathematical problems is animation media, which is closely related to engaging visual and auditory elements, thereby motivating students in the learning process. The aim of this research is to describe problem-solving skills in the topic of sets using animation media. This research is a type of descriptive study focusing on mathematical problem-solving skills, which is the variable of this research. The subject of this research is seventh-grade students at Muhammadiyah 4 Middle School in Palembang. Data was collected through two methods: written methods and interview methods. The research results indicate that the mathematical problem-solving ability of seventh-grade students at Muhammadiyah 4 Middle School in Palembang falls into the moderate category. By utilizing animated videos in mathematics learning on the topic of sets, it can assist students in solving or finding solutions to mathematical problems.